Arcs of Cyclic Order Three in the Conformal Plan - Gupta, Meera (My University, 1966)
Scope and Contents: This thesis is concerned with the properties of arcs of cyclic order three in the conformal plane. It establishes necessary and sufficient conditions for the union of two arcs of cyclic order three to be again an arc of cyclic order three, and for an arc of cyclic order three to be extensible to a larger arc of cyclic order three.
Keywords: arc; cyclic order; Mobius transformation